PERAN KEBIJAKAN DIVIDEN PADA PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR DI INDONESIA TAHUN 2015-2017) - Nathalia Kezia Deborah; Almatius Setya Marsudi (Prosiding Working Papers Series In Management, 2018)
The study attempted to examine the effect of divident as a moderator of the firm value - profitability relationship. Researchers see moderating effects of divident on the relationship between profitability and firm value. This paper uses data for fifty seven manufacturing industries in 2015-2017 in Indonesia, moderated regression analysis was conducted to see the role of moderation in the influence of profitability on firm value. We report two primary findings. First, The profitability contribute to the firm value, Second, there was no moderating effect of divident on the relationship between profitability and firm value..Keyword: Dividen Policy, Profitability, Corporate Value